2021
DOI: 10.2478/aut-2021-0037
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Standard Time of the Sewing Process using a Support Vector Machine with Particle Swarm Optimization

Abstract: Standard time is a key indicator to measure the production efficiency of the sewing department, and it plays a vital role in the production forecast for the apparel industry. In this article, the grey correlation analysis was adopted to identify seven sources as the main influencing factors for determination of the standard time in the sewing process, which are sewing length, stitch density, bending stiffness, fabric weight, production quantity, drape coefficient, and length of service. A novel forecasting mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Shao et al [21] tried the use of smart technology in the management of the sewing process, standard time in the process was predicted and computed, a machine learning prediction model was created, and model parameters were adjusted. Six factors such as sewing length, stitch density, bending stiffness, fabric weight, production amount, drape coefficient, and length of service were identified by correlation analysis.…”
Section: Related Research Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Shao et al [21] tried the use of smart technology in the management of the sewing process, standard time in the process was predicted and computed, a machine learning prediction model was created, and model parameters were adjusted. Six factors such as sewing length, stitch density, bending stiffness, fabric weight, production amount, drape coefficient, and length of service were identified by correlation analysis.…”
Section: Related Research Workmentioning
confidence: 99%
“…Next, a novel forecasting approach is put up to estimate the sewing process's standard time. By analyzing the performance using the mean-square error (MSE) and squared correlation coefficient, the suggested forecasting model is validated [21].…”
Section: Related Research Workmentioning
confidence: 99%
“…For example, the "air" node property is set to msg.payload.air to display the current air velocity. The output current is an important indicator for judging the state of the battery [11]. In this paper, whether the battery is in a state of peroxidation is judged by predicting the output current of the SOFCs.…”
Section: Monitoring Designmentioning
confidence: 99%
“…In addition, predicting abnormal measurement parameter data of fuel cells, such as charge/discharge current, charge/discharge voltage, humidification during operation, and gas pressure, can help identify possible faults in advance. Shao et al [11] used PSO to optimize the SVM algorithm for standard time-determined forecasting. The test results show that the square correlation coefficient is 0.917, and PSO-SVR can achieve a good prediction effect.…”
Section: Introductionmentioning
confidence: 99%
“…Y. Shao et al showed a strong correlation between the following parameters in the sewing process to determine sewing time: fabric weight, stitch density, drape coefficient, bending stiffness, seam length, production quantity and operating time [16].…”
Section: Introductionmentioning
confidence: 99%